1977
DOI: 10.1007/bf01252961
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and seasonal variations in human platelet serotonin in man

Abstract: Platelet serotonin (5-HT) was found to be an individually constant parameter correlating with the uptake of exogenous 5-HT. A pronounced diurnal pattern of 5-HT, with a minimum in the afternoon and higher values in the morning and evening, was similar to the diurnal variations in plasma free tryptophan. Platelet 5-HT was significantly higher at 8 a.m. than 4 p.m. in spring but no longer in autumn, and was similar in both men and women. It appeared that peripheral diurnal variations in 5-HT were opposite in ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…This is consistent with the notion that neuronal connections are unstable and labile during sleep, an idea supported by Cajal that is over 100 yea rs old (Azmitia , 2002). Since seroton in levels fluctuate over the year (Singh, 1964;Wirz-Justice et al, 1977), we can expect, although it has not been shown, that the capacity for learning and memory may show a similar fluctuation. What has been shown to fluctuate is the incidence of suicides (Bjorksten et al, 2005;Dreyer, 1959).…”
supporting
confidence: 75%
“…This is consistent with the notion that neuronal connections are unstable and labile during sleep, an idea supported by Cajal that is over 100 yea rs old (Azmitia , 2002). Since seroton in levels fluctuate over the year (Singh, 1964;Wirz-Justice et al, 1977), we can expect, although it has not been shown, that the capacity for learning and memory may show a similar fluctuation. What has been shown to fluctuate is the incidence of suicides (Bjorksten et al, 2005;Dreyer, 1959).…”
supporting
confidence: 75%
“…Blood was drawn and all platelet serotonin indices described below were conducted as part of the original published study (Cook et al, 1993). Although whole blood 5-HT levels are typically stable within individuals, some of the hyperserotonemic subjects showed instability and were not in the hyperserotonemic range when sampled at the time of the platelet assays, which may be related to the seasonal variation that has been described previously (Wirz-Justice et al, 1977;Hanna et al, 1998). The whole blood 5-HT level from the day of the platelet studies was used for analyses in the present study.…”
Section: Subjects and Blood Collectionmentioning
confidence: 99%
“…Previous work suggests that diet and/or fasting are unlikely to influence whole blood serotonin levels, 24 particularly when diet is as uniform as it is in the Hutterites. While time of sampling may affect whole blood serotonin levels, 25 nearly all of the blood sampling was done between 0900 h and noon. Similarly, an influence of seasonal variation on whole blood serotonin levels has been described, 25 but samples for these studies were collected during two consecutive winters.…”
Section: Measurement Of Whole Blood Serotoninmentioning
confidence: 99%
“…While time of sampling may affect whole blood serotonin levels, 25 nearly all of the blood sampling was done between 0900 h and noon. Similarly, an influence of seasonal variation on whole blood serotonin levels has been described, 25 but samples for these studies were collected during two consecutive winters. Further, the high heritability of whole blood serotonin in this population 13 suggests that diet, diurnal variation, and seasonal variation are unlikely to be confounding factors in this study.…”
Section: Measurement Of Whole Blood Serotoninmentioning
confidence: 99%